Biopolitics and Disciplinarity in the Legislation of Conduct in Public Spaces of Vilnius - Šupa, Maryja (Kriminologijos studijos, 2019)
This article presents the specific rhetoric of social control present in the sections of national and municipal legislation pertaining to conduct in public spaces of Vilnius, Lithuania. Theoretically, the paper utilises M. Foucault’s framework of power modalities both because of Foucault’s engaged questioning of power and the applicability of his insights to the spatial dimensions of the city. The paper bases its interpretive scheme on two premises: a) that law reveals biopolitical and disciplinary aspects of social control; and b) that urban public space presents a valuable case for the analysis of these aspects. A qualitative content analysis of national and municipal legislation has revealed that national legislation is driven by biopolitical objectives and municipal legislation by disciplinary ones. The national legislation focuses the regulation of public space on public order, public calm, and public dignity – public mores that must be upheld in the interest of the population and expanding beyond strictly public space. Disciplinarity is evident in municipal legislation insofar as it breaks space up into governable fragments, imposing painstakingly detailed prohibitions and obligations, and building a hierarchy inside the population between the desired and subnormal subject.